2004
DOI: 10.1080/03014223.2004.9518358
|View full text |Cite
|
Sign up to set email alerts
|

Predation by ants on jumping spiders (Araneae: Salticidae) in the Philippines

Abstract: Using a tropical fauna from the Philippines as a case study, ant-salticid predator-prey relationships were investigated. In the field, 41 observations of ant predation on salticids were made, and the actual attack on the salticid was seen in four. In the laboratory, five of the ant genera observed in the field were tested with four categories of salticids: (1) four myrmecophagic (i.e., ant-eating) species, (2) six myrmecomorphic (i.e., ant-like) species, (3) an ant-associate species (i.e., a species that is ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 27 publications
1
51
0
Order By: Relevance
“…Ants often prey on salticids (Nelson et al 2004) and, although comparable in size to typical salticid prey, ants have formidable defences, and many salticids identify ants by sight and avoid them (Nelson & Jackson 2006a), as an encounter with an ant is likely to end in the salticid's death (Nelson et al 2004). Myrmarachne is a genus of ant-like (myrmecomorphic) salticids and other salticids are also known to avoid Myrmarachne, apparently mistaking them for ants (Nelson & Jackson 2006a,b;Nelson & Jackson in press a).…”
Section: Introductionmentioning
confidence: 99%
“…Ants often prey on salticids (Nelson et al 2004) and, although comparable in size to typical salticid prey, ants have formidable defences, and many salticids identify ants by sight and avoid them (Nelson & Jackson 2006a), as an encounter with an ant is likely to end in the salticid's death (Nelson et al 2004). Myrmarachne is a genus of ant-like (myrmecomorphic) salticids and other salticids are also known to avoid Myrmarachne, apparently mistaking them for ants (Nelson & Jackson 2006a,b;Nelson & Jackson in press a).…”
Section: Introductionmentioning
confidence: 99%
“…Ants are notorious for both their abundance and their formidable defences [6], and it may not be surprising to find that among ant mimics there is considerable variation in form, ranging from accurate to imprecise mimicry. What is unusual is that here we have an example of a mimic resembling one of its own predators [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…The question of interest in this study is whether accuracy of ant mimicry, as judged by humans, is reflected in predator behaviour. The answer is of significance because most salticids will readily prey on each other [27], yet most salticids also appear to avoid ants [4], encounters with which are often lethal to salticids, including Myrmarachne [28,29]. Clearly, it is also pertinent to determine how nonhuman animals classify objects and to determine the differences (or not) that may be found according to very different visual systems.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, certain ants treat jumping spiders as potential prey. Some ants readily attacked and killed jumping spiders in laboratory conditions [27]. Halaj et al [28] showed that ants could affect the spider communities (especially wandering spiders) in Douglas fir, and the abundance of jumping spiders was higher in trees without ants.…”
Section: Introductionmentioning
confidence: 99%